Acute Anxiety Predicts Components of the Cold Shock Response on Cold Water Immersion: Toward an Integrated Psychophysiological Model of Acute Cold Water Survival - Barwood, Martin J.; Corbett, Jo; Massey, Heather; McMorris, Terry; Tipton, Mike; Wagstaff, Christopher R. D. (Frontiers in Psychology, 2018)
Introduction. Drowning is a leading cause of accidental death. In cold-water, sudden skin cooling triggers the life-threatening cold shock response (CSR). The CSR comprises tachycardia, peripheral vasoconstriction, hypertension, inspiratory gasp, and hyperventilation with the hyperventilatory component inducing hypocapnia and increasing risk of aspirating water to the lungs. Some CSR components can be reduced by habituation (i.e. reduced response to stimulus of same magnitude) induced by 3-5 short cold-water immersions (CWI). However, high levels of acute anxiety, a plausible emotion on CWI: magnifies the CSR in unhabituated participants, reverses habituated components of the CSR and prevents/delays habituation when high levels of anxiety are experienced concurrent to immersions suggesting anxiety is integral to the CSR. Purpose. To examine the predictive relationship that prior ratings of acute anxiety have with the CSR. Secondly, to examine whether anxiety ratings correlated with components of the CSR during immersion before and after induction of habituation. Methods. Forty-eight unhabituated participants completed one (CON1) seven-minute immersion in to cold water (15°C). Of that cohort, twenty-five completed four further CWIs that would ordinarily induce CSR habituation. They then completed two counter-balanced immersions where anxiety levels were increased (CWI-ANX) or were not manipulated (CON2). Acute anxiety and the cardiorespiratory responses (cardiac frequency [fc], respiratory frequency [fR], tidal volume [VT], minute ventilation [ ]) were measured. Multiple regression was used to identify components of the CSR from the most life-threatening period of immersion (1st minute) predicted by the anxiety rating prior to immersion. Relationships between anxiety rating and CSR components during immersion were assessed by correlation. Results. Anxiety rating predicted the fc component of the CSR in unhabituated participants (CON1;p<0.05,r=0.536,r2=0.190). After habituation immersions (i.e. cohort 2), anxiety rating predicted the fR component of the CSR when anxiety levels were lowered (CON2;p<0.05,r=0.566,r2=0.320) but predicted the fc component of the CSR (p<0.05,r=0.518,r2=0.197) when anxiety was increased suggesting different drivers of the CSR when anxiety levels were manipulated; correlation data supported these relationships. Discussion. Acute anxiety is integral to the CSR before and after habituation. We offer a new integrated model including neuroanatomical, perceptual and attentional components of the CSR to explain these data.